Coping strategies used by university students with disability: a systematic review - Rafael Carballo; Therese M. Cumming (Cogent Education)
There are currently a large number of studies that focus on analysing the difficulties encountered by students with disability at university. However, there is a need for more knowledge about the coping strategies that students find helpful and how universities can promote and support their use. This systematic review analyses the scientific literature on coping strategies used by university students with disability during their academic careers. The review analyses 17 studies that included a total of 674 students with disability as participants and analysed their coping strategies. The results of the analysis of these studies compiled the different types of coping strategies that participants used to successfully complete their studies. In addition, recommendations are drawn for Higher Education institutions to improve the academic experience of students with disability through the promotion and support of these strategies. The results of this study highlight the reality of the hardships experienced by university students when having to make certain efforts due to their disability, as well as the need for institutions to offer greater support to facilitate their university experience.